Libraries traveling to Nicaragua - Reyes Reyes, Johana (1980)
The inability to establish permanent libraries in Nicaragua, raises the need to promote the creation of mobile libraries that they could cover big air geographical taking books towards whom they cannot have readings. This will reaffirm the aspirations of the Revolutionary Government, of which the education occupies a basic place in our country.